Search for electroweak production of a vector-like quark decaying to a top quark and a Higgs boson using boosted topologies in fully hadronic final states - The, C. M. S. collaboration; Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Asilar, E.; Bergauer, T.; Brandstetter, J.; Brondolin, E.; Dragicevic, M.; Erö, J.; Flechl, M.; Friedl, M.; et al. (My University, 2017)
A search is performed for electroweak production of a vector-like top quark partner T of charge 2/3 in association with a standard model top or bottom quark, using 2.3 fb?1 of proton-proton collision data at s=13 TeV collected by the CMS experiment at the CERN LHC. The search targets T quarks decaying to a top quark and a Higgs boson in fully hadronic final states. For a T quark with mass above 1 TeV the daughter top quark and Higgs boson are highly Lorentz-boosted and can each appear as a single hadronic jet. Jet substructure and b tagging techniques are used to identify the top quark and Higgs boson jets, and to suppress the standard model backgrounds. An excess of events is searched for in the T quark candidate mass distribution in the data, which is found to be consistent with the expected backgrounds. Upper limits at 95% confidence level are set on the product of the single T quark production cross sections and the branching fraction ? (T ? t H) , and these vary between 0.31 and 0.93 pb for T quark masses in the range 1000-1800 GeV. This is the first search for single electroweak production of a vector-like T quark in fully hadronic final states.[Figure not available: see fulltext.]. © 2017, The Author(s).
Citation: The, C. M. S. c., Sirunyan, A. M., Tumasyan, A., Adam, W., Asilar, E., Bergauer, T., . . . Woods, N. (2017). Search for electroweak production of a vector-like quark decaying to a top quark and a Higgs boson using boosted topologies in fully hadronic final states. Journal of High Energy Physics, 2017(4). doi:10.1007/JHEP04(2017)136
Keywords: Beyond Standard Model; Hadron-Hadron Scattering (Experiments); Top Physics